Plaidoyer for den destruktive karakter - Andreasen, Torsten; Day, James (K&K - Kultur og Klasse, 2016)
‘For too long the accent was placed on creativity’ says Benjamin in his essay on Karl Krauss, written at the beginning of the thirties. In this ‘plaidoyer’ we argue for a destructive critical practice precipitated by the current crisis faced by critique. Following a bare-bones account in which this crisis is traced back to the 1930s, we turn to Benjamin’s destructive character (most obviously present in his 1931 article of the same name, but to be encountered throughout his writing) to plead for a deeply negative form of critique. After the uncoupling of critique from the revolutionary organizations of the 1930s, the negativity of critical writing was subsequently lost and predominantly affirmative, post-critical positions carried the day after the defeats of 1968. This has resulted in a divorce between critical writing and possible material change, which has greatly narrowed the critical horizon, by and large anchored within the university. Rather than seeking to find new institutional supports for critique or any kind of critical apparatus, Benjamin’s destructive character points towards the clearing away of the status quo.